In situ detoxification of lignocellulosic hydrolysate using a surfactant for butyric acid production by Clostridium tyrobutyricum ATCC 25755. Issue 4 (April 2015) - Lee, Kyung Min; Kim, Ki-Yeon; Choi, Okkyoung; Woo, Han Min; Kim, Yunje; Han, Sung Ok; Sang, Byoung-In; Um, Youngsoon
Highlights A simple in situ detoxification method for lignocellulosic hydrolysate was developed. Adding Tween 80 during butyric acid fermentation detoxified p-coumaric and ferulic acids. Detoxification effect of Tween 80 was correlated with the hydrophobicity of phenolics. Detoxification method was verified with rice straw hydrolysate for butyric acid production. This is the first report of simultaneous detoxification and fermentation using a surfactant.